Assessment and treatment of tracheostomy tube manipulation: Effects of competing stimuli and protective equipment. Issue 4 (21st May 2021) - Falligant, John M.; Hardesty, Samantha L.; Pierce, David; Kurtz, Patricia F.
Abstract : Functional analyses (FA) are widely used in the assessment and treatment of problem behavior. However, with limited exceptions, the procedures are rarely applied to potentially dangerous behaviors involving medical equipment. The current study replicated and extended procedures previously used by Kurtz and Chin (2004) to assess and treat tracheostomy tube manipulation in a 5‐year‐old boy diagnosed with extensive medical and developmental conditions. FA results indicated that tracheostomy tube manipulation (i.e., touching, pulling, occluding) was automatically maintained. An augmented competing stimulus assessment was conducted to identify stimuli associated with low levels of tracheostomy tube manipulation and elevated levels of item engagement. A treatment package consisting of noncontingent access to competing stimuli with prompting and continuous application of protective equipment produced significant reductions in tracheostomy tube manipulation, as well as significant increases in toy engagement.